Uneven geographies in the various language editions of Wikipedia: the case of Ukrainian cities - Gnatiuk, Oleksiy; Glybovets, Victoria (Hungarian Geographical Bulletin, 2021)
The paper tackles the issue of uneven geographical representations on Wikipedia, the most visible and powerful user-generated encyclopaedia. In particular, it addresses language imbalances on Wikipedia with regard to geographical information and uneven spatial patterns of territory coverage on the different language versions in an attempt to verify expectations about the cultural factors that influence these imbalances and uneven spatial patterns. Ukraine is a promising case for testing the formulated expectations, as it has a large number of neighbouring countries, and most of them had political and cultural influence on its territory in the past. The volumes (word counts) of articles about the Ukrainian cities were analysed for seven language versions of Wikipedia, including the Ukrainian version and the versions of all bordering countries. The results show that historical geography is the strongest and central factor, and most of the key relic borders (former boundaries) can be traced. Ethnic composition appears to be another important factor, although weaker than the previous one. The role of the border factor is often unclear, but in some cases it definitely makes an impact and therefore cannot be completely ignored. Thus, the geographies of Wikipedia are not indifferent to the issues of ethnicity and geopolitics. The research calls into question the ability of modern Wikipedia to be a reliable and balanced source of geographical knowledge, as the described imbalances may create lopsided and biased geographical representations in people from different countries and nations.